Comparação entre os estratos arbóreo e de regeneração na mata de galeria da Estação Ecológica do Panga, Uberlândia-MG - Mendes, Simone (2002)
The protection, which gallery forests and other riverine formations supply to watercourses, assigns to them an important role in permanent environmental conservation. This fact, however, does not impede degradation of these environments. On the other hand, it stimulates ecological studies of the few remaining areas. In order to contribute to these studies, our research aims at comparing the arboreal and regeneration strata of tree species in a gallery forest, in order to estimate probable community changes. This study was carried out in the ‘'Estação Ecológica do Panga” (EEP), Uberlândia-MG. We made inventories of two different strata: the arboreal stratum (EA) and the regeneration stratum (ER). The EA sample included 43 permanent plots (lOm x lOm), where all individuais with circumference > 15 cm at breast height (cbh) were recorded. The inventory of ER included 40 out of the 43 plots used in EA. We registered all individuais with a height > lm, even those that were not included in the EA study. Height and spatial distributions of the most important species of the two strata were defined. Of the 114 species encountered, 51 were common to both strata, 16 exclusively occurred in EA and 23 only in ER. Another 5 species of EA and 19 of ER were not yet identifíed to species levei. Some species were well represented in both stratra, e.g., Calophyllum brasiliense, Copaifera langsdorffii, Talauma ovata, Linociera arbórea and Aspidosperma cylindrocarpon. Others, like Tapirira guianensis, Luehea divaricata, Tabebuia umbellata and Croíon unicurana, were rare or even missing in ER. Endlicheria paniculata, Calyptranthes widigrenianum, and Eugenia florida, on the other hand, were more common in ER. Although the criteria used for the inclusion of plants into ER has favoured understorey species, a comparison of floristic and phytosociological data as well as of height distribution between the two strata indicates that the future community structure will be similar to that actually encountered in the gallery forest of EEP - given that environmental conditions remain unchanged. The clustered distribution pattern of species in the ER indicates that the establishment of a plant depends on the mosaic of environmental factors prevailing in the actual EEP gallery forest.